PENGARUH RASA INGIN TAHU TERHADAP KARAKTER RELIGIUS ANAK SEKOLAH MINGGU KECAMATAN UKUI - Andriana, Nanda; Ayub, Daeng; Fitrilinda, Dafetta (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
His study aims to determine and analyze the influence of curiosity on the religious character of Sunday School children in Ukui District. The background of the study shows that many children are still passive and show less curiosity about spiritual learning, which has an impact on the low understanding and application of religious values in everyday life. Method: This study uses a quantitative approach with an ex post facto type. The study population consisted of 105 Sunday School children, and a sample of 83 respondents was obtained using the Simple Random Sampling technique. The research instrument was a questionnaire that measured two variables, namely curiosity (X) and religious character (Y), which were compiled based on relevant theories and indicators, and tested for validity and reliability. Results: The analysis showed a positive and significant influence between curiosity on the religious character of Sunday School children. The contribution of this influence was 59.60% with a moderate interpretation, while 40.40% was influenced by other factors outside this study. Novelty: This study confirms that developing curiosity through interactive and exploratory learning in Sunday School can improve children's understanding of faith, devotion to worship, and character development. The results of this study can serve as a basis for church educators in designing learning strategies that foster curiosity as a means of developing children's religious character.